2022
DOI: 10.1093/brain/awac061
|View full text |Cite
|
Sign up to set email alerts
|

Host oligodendrogliopathy and α-synuclein strains dictate disease severity in multiple system atrophy

Abstract: Multiple system atrophy is a progressive neurodegenerative disease with prominent autonomic and motor features. During early stages different subtypes of multiple system atrophy are distinguished by their predominant parkinsonian or cerebellar symptoms reflecting the heterogeneous nature of the disease. The pathognomonic feature of multiple system atrophy is the presence of ɑ-synuclein (ɑSyn) protein deposits in oligodendroglial cells. ɑSyn can assemble in specific cellular or disease environments and form ɑSy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 65 publications
(91 reference statements)
0
7
0
Order By: Relevance
“…The general notion from an increasing number of studies using a-syn spreading models confirms that healthy oligodendrocytes are not readily accumulating fibrillar a-syn in their cytoplasm and possibly a preceding oligodendroglial dysfunction is needed to trigger the GCI formation. This has been supported by a recent experiment, in which only transgenic mice with oligodendroglial a-syn overexpression which get intracerebral inoculation of a-syn polymorphs are prone to accelerating an MSA-like phenotype in a strain-dependent manner [73]. The a-syn spreading models are crucial for understanding the specific features of protein misfolding and properties in MSA versus other synucleinopathies, and thus shed light on pathogenic mechanisms involved in the progression of the disease [74].…”
Section: Classes Of Msa Models and Their Relevancementioning
confidence: 88%
“…The general notion from an increasing number of studies using a-syn spreading models confirms that healthy oligodendrocytes are not readily accumulating fibrillar a-syn in their cytoplasm and possibly a preceding oligodendroglial dysfunction is needed to trigger the GCI formation. This has been supported by a recent experiment, in which only transgenic mice with oligodendroglial a-syn overexpression which get intracerebral inoculation of a-syn polymorphs are prone to accelerating an MSA-like phenotype in a strain-dependent manner [73]. The a-syn spreading models are crucial for understanding the specific features of protein misfolding and properties in MSA versus other synucleinopathies, and thus shed light on pathogenic mechanisms involved in the progression of the disease [74].…”
Section: Classes Of Msa Models and Their Relevancementioning
confidence: 88%
“…These spinal tracts are among the earliest to be affected in MSA and connect the urogenital nerves and the spinal cord to the midbrain and cerebellum. Since the propagation of ɑSyn in MSA requires the expression of oligodendroglial ɑSyn [52,62], we used a humanized ɑSyn model (hu-ɑSyn mice) to study MSA progression. Hu-ɑSyn mice lack murine ɑSyn and only express human ɑSyn, at levels comparable to those seen in WT mice [20].…”
Section: Aggregated ɑSyn Propagates From the Urinary Bladdermentioning
confidence: 99%
“…Oligodendrocytes normally express low levels of ɑSyn [3,13,14,28]. Aggregation of ɑSyn in oligodendrocytes leads to the assembly of disease-specific ɑSyn fibrils with highly aggregation-prone features [52,62]. In MSA patients, aggregates of ɑSyn are also detected in spinal cord oligodendrocytes and Schwann cells of the spinal nerves [6,42].…”
Section: Introductionmentioning
confidence: 99%
“…[27] The effect of Ptzyme alone is not sufficient for achieving wholistic disease therapy, as it has defects in achieving mild regulation of the inflammatory microenvironment. [28][29][30] Microglia has been implicated in the regulation of inflammatory microenvironment in the brain, thus playing cardinal part in regulating the development, homeostasis, and degeneration of the central nervous system (CNS). [31,32] Studies have found that under the treatment of anti-inflammation small molecule compounds like quercetin (Que), the microglia could switch from pro-inflammatory M1 phenotype to the anti-inflammatory M2phenotype, thus affording a desirable solution for regulating inflammatory microenvironment.…”
Section: Introductionmentioning
confidence: 99%